Back Cover: Fluorophore‐Labeled Cyclooxygenase‐2 Inhibitors for the Imaging of Cyclooxygenase‐2 Overexpression in Cancer: Synthesis and Biological Studies (ChemMedChem 1/2014). Issue 1 (January 2014) - Bhardwaj, Atul; Kaur, Jatinder; Wuest, Frank; Knaus, Edward E.
<x xml:space="preserve">Abstract</x> The back cover picture shows a molecular model of an imaging agent (top left), which can be used as a specific biomarker for fluorescence imaging of cyclooxygenase‐2 in human colon cancer cells. The results of this study will open new avenues for the development of noninvasive fluorescent biomarkers for imaging and diagnosis of disease states in which cyclooxygenase‐2 is overexpressed. For further details, see the Full Paper by Frank Wuest, Edward E. Knaus et al. on p. 109 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>